Integrated proteomics and metabolomics analysis of rice leaves in response to rice straw return - Yan, Shuangshuang; Gong, Shengdan; Sun, Kexin; Li, Jinwang; Zhang, Hongming; Fan, Jinsheng; Gong, Zhenping; Zhang, Zhongxue; Yan, Chao (Frontiers in Plant Science, 2022)
Straw return is crucial for the sustainable development of rice planting, but no consistent results were observed about the effect of straw return on rice growth. To investigate the response of rice leaves to rice straw return in Northeast China, two treatments were set, no straw return (S0) and rice straw return (SR). We analyzed the physiological index of rice leaves and measured differentially expressed protein (DEPs) and differentially expressed metabolites (DEMs) levels in rice leaves by the use of proteomics and metabolomics approaches. The results showed that, compared with the S0 treatment, the SR treatment significantly decreased the dry weight of rice plants and nonstructural carbohydrate contents and destroyed the chloroplast ultrastructure. In rice leaves of SR treatment, 329 DEPs were upregulated, 303 DEPs were downregulated, 44 DEMs were upregulated, and 71 DEMs were downregulated. These DEPs were mainly involved in photosynthesis and oxidative phosphorylation, and DEMs were mainly involved in alpha-linolenic acid metabolism, galactose metabolism, glycerophospholipid metabolism, pentose and gluconic acid metabolism and other metabolic pathways. Rice straw return promoted the accumulation of scavenging substances of active oxygen and osmotic adjustment substances, such as glutathione, organic acids, amino acids, and other substances. The SR treatment reduced the photosynthetic capacity and energy production of carbon metabolism, inhibiting the growth of rice plants, while the increase of metabolites involved in defense against abiotic stress enhanced the adaptability of rice plants to straw return stress.